1996
DOI: 10.1177/096032719601500902
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the potential carcinogenicity and genetic toxicity to humans of the herbicide acetochlor

Abstract: Comprehensive toxicological studies of the herbicide acetochlor are presented and discussed. Although it gave a negative profile of responses in the many toxicity tests conducted there were some findings that prompted further investigation. First, although non-mutagenic in the Sal monella assay, acetochlor was clastogenic to mammalian cells treated in vitro. This clastogenic potential was not expressed in vivo in four rodent cytogenetic assays (bone marrow and germ cells). Second, although acetochlor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 33 publications
1
36
1
Order By: Relevance
“…Despite a clear association between TH responsiveness and acetochlor action for many genes, not all T 3 -regulated genes are targets of acetochlor in X. laevis. In rats, studies have shown that acetochlor acts by increasing T 4 clearance from the liver, thereby reducing TH levels (Ashby et al 1996;Wilson et al 1996). This mechanism appears to be incompatible with our observations and those of others.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Despite a clear association between TH responsiveness and acetochlor action for many genes, not all T 3 -regulated genes are targets of acetochlor in X. laevis. In rats, studies have shown that acetochlor acts by increasing T 4 clearance from the liver, thereby reducing TH levels (Ashby et al 1996;Wilson et al 1996). This mechanism appears to be incompatible with our observations and those of others.…”
Section: Discussioncontrasting
confidence: 82%
“…The preemergent herbicide acetochlor [2-chloro-N-(ethoxy-methyl)-N-(2-ethyl-6-methylphenyl) acetamide] is a persistent organic pollutant (POP) that can be detected in shallow ground water 1 year after field application, and there is evidence that it can act as an EDC (Ashby et al 1996;Barbash et al 1999;Cheek et al 1999a;Veldhoen and Helbing 2001;Wilson et al 1996). Acetochlor was introduced in 1994, and its use in agriculture has increased approximately 32% measured as the number of pounds applied annually (from 1994 to 2000).…”
mentioning
confidence: 99%
“…Acetochlor induces nasal tumors in rats at the maximumtolerated dose of 1000 parts per million and is classified as ''likely to be carcinogenic to humans'' by the US EPA (Ashby et al, 1996;Dearfield et al, 1999). In human and rat liver microsomes, acetochlor is bioactivated via a multistep pathway to the putative DNA-reactive metabolite, 2-methyl-6-ethylbenzoquinoneimine (Jefferies et al, 1998;Coleman et al, 2000;Green et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the rat, a series of GSH-associated biliary metabolites are formed which are not produced in the mouse, which are resistant to the nasal adenoma induction. Thyroid tumors were observed in rats exposed to the supra-MTD dose of acetochlor and developed by the mechanism described above, i.e., decrease of thyroid hormone and increased level of pituitary TSH [40].…”
Section: Various Pesticidesmentioning
confidence: 99%